A new Nototriton (Caudata: Plethodontidae) from Parque Nacional Montaña de Botaderos in northeastern Honduras - Townsend, Josiah H.; Medina-Flores, Melissa; Reyes-Calderón, Onán; Austin, James D. (Zootaxa, 2013)
The highlands of northeastern Honduras remain under-characterized in terms of biological diversity, as exemplified by the regularity of new amphibian and reptile taxa discoveries. Following the recent description of a new species of Nototriton from the Sierra de Agalta in northeastern Honduras, we report the discovery of a second new species of Nototriton from the nearby Parque Nacional Montaña de Botaderos. This new taxon, Nototriton mime sp. nov., is distinguished from other Nototriton by its distinctive pale brown dorsal coloration in adult males, relatively large nares, a relatively broad head, mitochondrial sequence divergence, and phylogenetic relationships, and is geographically isolated from other populations of Nototriton.